Corneal epithelial inclusion cysts in 12 dogs (13 eyes) from 2010 to 2019: A multicentric retrospective study. (1st August 2020) - Cassagnes, Charles; Cognard, Sophie Andree; Nicolier, Alexandra; Cazalot, Guillaume; Dossin, Evelyne; Durieux, Philippe; Goulle, Frédéric; Michel, Julien; Pilorge, Philippe; Verneuil, Marc; Isard, Pierre‐François; Mathieson, Iona; et al.
Abstract: Objective: The aim of this retrospective study was to review the clinical data and outcomes of patients that suffered corneal epithelial inclusion cysts (CEIC). Animals studied Thirteen eyes from 12 dogs from multiple private practices in France and Belgium, with a strong clinical of CEIC were included in the study. Results: The mean age of affected dogs was 9 years. There were 9 females and 3 males. Two out of 12 dogs were Shih Tzus. Where identified, etiology was traumatic. Eleven dogs were affected unilaterally, 1 bilaterally. The cysts were single, bi‐lobulated, or tri‐lobulate, and cyst size ranged from 1 to 6 mm in diameter. Keratectomy alone was performed in seven cases, in conjunction with a conjunctival graft in three cases, a porcine small intestine mucosa graft in two cases, or an amniotic membrane graft in one case. Histopathologic findings were consistent in all eyes with a cyst located in the corneal stroma, composed of a nonkeratinized squamous epithelium delineating a lumen filled with neutrophils and desquamated epithelial cells. Surgery was curative in all cases but one, where the removal was incomplete and recurrence occurred several weeks after the surgery. Conclusion: Corneal epithelial inclusion cysts is a rare condition, secondary to corneal trauma, which can be treated successfully with conventional keratectomy alone or in conjunction with graft procedures.